-22=9+7(k-2)

Simple and best practice solution for -22=9+7(k-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -22=9+7(k-2) equation:


Simplifying
-22 = 9 + 7(k + -2)

Reorder the terms:
-22 = 9 + 7(-2 + k)
-22 = 9 + (-2 * 7 + k * 7)
-22 = 9 + (-14 + 7k)

Combine like terms: 9 + -14 = -5
-22 = -5 + 7k

Solving
-22 = -5 + 7k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-7k' to each side of the equation.
-22 + -7k = -5 + 7k + -7k

Combine like terms: 7k + -7k = 0
-22 + -7k = -5 + 0
-22 + -7k = -5

Add '22' to each side of the equation.
-22 + 22 + -7k = -5 + 22

Combine like terms: -22 + 22 = 0
0 + -7k = -5 + 22
-7k = -5 + 22

Combine like terms: -5 + 22 = 17
-7k = 17

Divide each side by '-7'.
k = -2.428571429

Simplifying
k = -2.428571429

See similar equations:

| 7n-3=60 | | -3(1x+8)=-15 | | -6f-3f=-27 | | f(x)=4x+5(sin^4)x | | b-3.2=1.5 | | -3(1x+8)=15 | | z+4-3=2z | | 123=5x-2(-2x-12) | | 8x-7=2(2+7)-5 | | -v+8=-(v-4) | | 2n+3=n+12 | | -2-5(1-3x)=30 | | 5x^2+12x-39991=0 | | -6(1x+4)=-42 | | (-12)(-6.9)9.5=X(9.5)(-12.3) | | 2m+3m=30 | | -8(1x-1)+8=-2x+64 | | 5m+3-12m=-(7m-14)+6 | | Z-81.6=-18.6 | | -(.66)(-0.3x)(1.5)(-1)= | | -(.625)(5x)(1.6)(12y)(0)= | | 5(1x+6)+13=5x+43 | | 9-5+1=15 | | 5x-4forx=3 | | 3xx=6 | | 47=3x+5 | | (3x-7)(x-4)=0 | | -6x+12=-5x+19 | | 3x-4iy=9+22i | | 7+2x-x=9+3x | | -22+26= | | 65=-5x-10 |

Equations solver categories